Suspensions of Colloidal Particles and Aggregates - Babick, Frank; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book addresses the properties of particles in colloidal suspensions. It has a focus on particle aggregates and the dependency of their physical behaviour on morphological parameters. For this purpose, relevant theories and methodological tools are reviewed and applied to selected examples. The book is divided into four main chapters. The first of them introduces important measurement techniques for the determination of particle size and interfacial properties in colloidal suspensions. A further chapter is devoted to the physico-chemical properties of colloidal particles-highlighting the interfacial phenomena and the corresponding interactions between particles. The book's central chapter examines the structure-property relations of colloidal aggregates. This comprises concepts to quantify size and structure of aggregates, models and numerical tools for calculating the (light) scattering and hydrodynamic properties of aggregates, and a discussion on van-der-Waals and double layer interactions between aggregates. It is illustrated how such knowledge may significantly enhance the characterisation of colloidal suspensions. The final part of the book refers to the information, ideas and concepts already presented in order to address technical aspects of the preparation of colloidal suspensions-in particular the performance of relevant dispersion techniques and the stability of colloidal suspensions.
Introduction -- Characterisation of colloidal suspensions -- Fundamentals in colloid science -- Suspensions of colloidal aggregates -- Dispersion of colloidal suspensions and their stability -- Summary and conclusion.
Keywords: Fluid mechanics; Soft condensed matter; Materials -- Analysis; Physical chemistry; Mechanics, Applied; Solids; Engineering Fluid Dynamics; Soft and Granular Matter; Characterization and Analytical Technique; Physical Chemistry; Solid Mechanics